Detection of Specific IgG-Antibodies Against Toxoplasma gondii in the Serum and Milk of Domestic Donkeys During Lactation in China: A Potential Public Health Concern - Chen, Long; Zhao, Zi-Jian; Meng, Qing-Feng (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii is a worldwide zoonotic protozoan. Donkeys are often susceptible to many pathological agents, acting as carriers of pathogens for other animal species and humans. However, data on the prevalence of T. gondii in donkeys during lactation and on the status of antibodies against T. gondii in donkey milk are lacking. A cross-sectional study evaluated the variation of the anti-T. gondii antibodies in the blood and milk of domestic donkeys during lactation. A total of 418 domestic donkeys were randomly selected from the Shandong province, eastern China from January 2019 to March 2020. The anti-T. gondii antibodies were found in 11.72% (49/418) serum and 9.81% (41/418) milk samples using a commercial ELISA kit, respectively. There was a very high consistency between the serum and milk (Spearman’s coefficient = 0.858, p-value < 0.0001 and Kendall’s tau = 0.688, p-value < 0.0001), particularly at the 45th to 60th day of lactation. The present results of the statistical analysis showed that the history of abortion (p = 0.026; adjusted OR = 2.20; 95% CI: 1.15–4.20) and cat in the house (p = 0.008; adjusted OR = 2.36; 95% CI: 1.26–4.44) were significantly associated with T. gondii infection in the domestic donkeys. This is the first report to detect antibodies against T. gondii in donkey milk in China. These results indicate a potential risk of humans contracting the infection through the consumption of raw milk from the naturally infected donkeys.